The Portrayal Of Jesse Owens’ Character As The Representation Of Male African-American Athlete In Stephen Hopkins’ Race (2016): New Historicism - Zakiyah Dania Billah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
In the 1930s, African-American male athletes faced segregation and discrimination due to their skin color. Modern biographical films now offer a more accurate representation of their struggles and achievements. This research examines how the movie “Race” (2016) portrays Jesse Owens, a male African-American athlete from the 1930s, and its implications for present-day US race relations. Through qualitative analysis using Narrative and Non-Narrative methods, we apply Stephen Greenblatt’s New Historicism to explore the movie's depiction of Owens. By comparing the film to historical records, we find that